PENGEMBANGAN SUMBERDAYA PETUGAS PENYULUH LAPANGAN PPL PERTANIAN GUNA MENGHADAPI PERSAINGAN DAN MERAIH PELUANG KERJA (THE DEVELOPMENT OF AGRICULTURE EXTENSION WORKER RESOURCES TO FACE COMPETITION AND TO GET JOB OPPORTUNITY) - Herbenu, PC. (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2007)
Current vision of agribusiness development is to build a creative, productive and healthy society through a strong and local resourced-based agricultural development. Its mission is to provide food supply, empower human resources, and create employment and economic opportunities, and to sustain and utilise natural resources with responsible manner. Realization of this mission is, however, undermined by low education (more than 80% was in elementary level, even in completed). It results in blurred vision of farmer in doing business and weak entrepreneurship. On of necessary efforts to cope with this problem is to recruit more university students for field advisor of agriculture (PPL), instead of current field advisor with only senior high school level of education. For this purpose, university should create a curriculum program that is aimed at developing entrepreneurship skills for its students. University should be able to produce well-prepared graduated students with entrepreneurship skills, knowledgeable, religious capacity, and nationalism. Keywords: ,